2023
DOI: 10.3390/s23020886
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Temperature Correction of Medical Range Fiber Bragg Gratings Dosimeters

Abstract: The interest in fiber Bragg gratings dosimeters for radiotherapy dosimetry lies in their (i) submillimeter size, (ii) multi-points dose measurements, and (iii) customizable spatial resolution. However, since the radiation measurement relies on the thermal expansion of the surrounding polymer coating, such sensors are strongly temperature dependent, which needs to be accounted for; otherwise, the errors on measurements can be higher than the measurements themselves. In this paper, we test and compare four techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Consequently, according to this model, our FBG dosimeter is measuring the temperature change induced by absorbed radiation, 21 otherwise known as absorbed dose calorimetry. Centering a 20 cm long detector (having one FBG positioned every cm) on a 10 ×$\times$ 10 cm2$^{2}$ field, we have also previously shown that FBGs located outside the irradiation field respond solely to ambient temperature variations, whereas FBGs located inside the irradiation field responded to both ambient temperature and radiation‐induced temperature variations 30 . The collective findings, along with the close alignment between the post‐irradiation signal and the thermal simulation presented in this work, confirm that our FBG detector is effectively measuring a radiation‐induced temperature increase and is therefore, a calorimeter, which is not surprising since FBGs are common temperature sensors.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Consequently, according to this model, our FBG dosimeter is measuring the temperature change induced by absorbed radiation, 21 otherwise known as absorbed dose calorimetry. Centering a 20 cm long detector (having one FBG positioned every cm) on a 10 ×$\times$ 10 cm2$^{2}$ field, we have also previously shown that FBGs located outside the irradiation field respond solely to ambient temperature variations, whereas FBGs located inside the irradiation field responded to both ambient temperature and radiation‐induced temperature variations 30 . The collective findings, along with the close alignment between the post‐irradiation signal and the thermal simulation presented in this work, confirm that our FBG detector is effectively measuring a radiation‐induced temperature increase and is therefore, a calorimeter, which is not surprising since FBGs are common temperature sensors.…”
Section: Discussionmentioning
confidence: 95%
“…Figure 2 presents the Bragg wavelength before, during and after a 20 Gy irradiation. To smooth the detector signal, three methods are compared on the figure: a linear fit during irradiation (post‐irradiation technique), a rolling mean with the nine previous values (real‐time technique compatible with real‐time interpolated temperature gradient for multi‐point dosimetry temperature correction technique 30 ) and a linear digital filter scipy.signal.filtfilt (post‐irradiation technique). For each technique, a mean difference between the measured wavelength and the detector response are respectively (7 ±$\pm$ 6)%, (4 ±$\pm$ 3)% and (4 ±$\pm$ 2)%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations